A magyarországi makedonisztika - Kuzder, Rita (Slavia Centralis, 2020)
In this paper on Macedonian studies in Hungary, I first describe the historical relationship between these two nations in broad terms. This summary is followed by an outline of all Macedonian literary works published since 1814, in chronological order. Included in this historical outline of Macedonian literature are summaries of the history of literature, lectures on Macedonian literature, news about Macedonian writers and the prize-winners of Macedonian literary festivals. I also highlight the work of the most notable translators, i.e., Pascal Gilevski,Zoltán Csuka, Romána Gimes and Annamária Czinege-Panzova, who plays an important role even today.
Keywords: Hungarian literature; Macedonian literature; Pascal Gilevski; Zoltán Csuka; Blaze Koneski; translation work